The Learning to Be Project: An Intervention for Spanish Students in Primary Education - Resurrección, Davinia M.; Jiménez, Óliver; Menor, Esther; Ruiz-Aranda, Desireé (Frontiers in Psychology, 2021)
Despite the emphasis placed by most curricula in the development of social and emotional competencies in education, there seems to be a general lack of knowledge of methods that integrate strategies for assessing these competencies into existing educational practices. Previous research has shown that the development of social and emotional competencies in children has multiple benefits, as they seem to contribute to better physical and mental health, an increase in academic motivation, and the well-being and healthy social progress of children. This study aims at assessing the possible changes in children’s self-esteem, socio-emotional competencies, and school-related variables after participating in the Learning to Be project (L2B) project. Methods: This quasi-experimental study included an intervention group (L2B) and a control group. The participants were 221 students in primary education (55.2% girls) between the ages of eight and 11 (M = 9.31; SD = 0.89). The L2B intervention program took place over a period of 5 months. The assessment was carried out twice, before and after the intervention through three main evaluation instruments: the Rosenberg’s Self-Esteem questionnaire, the Socio-Emotional competence questionnaire (SEQ), and self-report scales for measuring school difficulties, school engagement, opinions about school, and school absence. Ten schools from different Spanish provinces participated. Results: The results indicate that those participants in the experimental group show higher self-esteem, better responsible decisions, and higher self-awareness than those in the control group. There were no other statistical differences between groups. Conclusions: The results of this work suggest that the implementation of the L2B program did not improve social and emotional competencies in primary school students. Further research related to how include formative assessment in SEL programs is needed.